Lithuanian production modeling - Bratčikovienė, Nomeda (Lietuvos matematikos rinkinys, 2005)
Possibilities of production and its components in Lithuania modeling were analyzed in this paper. It is important to do good forecasts for production. Indicators which have strong influence on production were found. The obtained models explain structure of production and its components. They can be applied for short-term forecasting.